The Development Process of Problem Based Learning Models Developed by Exposition Text Writing Materials on VIII Grade Students of Methodist 12 Medan - Putri Dewita Napitupulu; Mutsyuhito Solin; Abdurahman Adisaputera (BIRCU, 2019)
This study is aimed to describe the development process of problem based learning models developed by exposition text writing materials on students. One of the models used by teachers in learning of exposition text writing was a problem based learning model. The teacher applies a problem based learning model in text learning but has obstacles when implementing the syntax of the learning model. This research was conducted at Junior high school of Methodist 12 Medan in July to August 2019. The research that has been carried out is a research and development that using the 4-D method which takes four stages of research, namely Define, design, development, and dissemination. The product of this research was in the form of developing the steps of a problem based learning model. The result shows that the aspects of the assessment given by reviewers, the product design of the problem based learning model development has been very good with an average score of overall acquisition of 80% with very good assessment criteria.